The Challenge of Demand in Poor Community In Mariso District, Makassar City - Nur Setiawati Mappaselleng; H Bisyri Abdul Karim (Lembaga Sembilan Tiga Community, 2020)
This study aims to identify the challenges of da'wah faced in carrying out da'wah activities in poor communities in Mariso sub-district, Makassar city. These challenges are examined in the context of Da'wah communication by identifying research questions who are the coveted figures in Da'wah activities, what Da'wah messages are needed and what Da'wah methods are practical, desirable and easily accessible. This research approach uses a mixture of qualitative and quantitative research methods. Data collection was carried out through literature study, field observations, use of questionnaires, and in-depth interviews. Description and analysis of data using the Da'wah communication approach. The results of the research show that the majority of the poor people of the Mariso sub-district still crave the figure of Mr. Imam as a source or communicator in propaganda activities. This was followed by some hopes for community organizations and the government and a small portion only for individuals. Regarding the message of da'wah, the theme of worship is more desirable than the theme of good deeds, family, work, and hospitality. While the method of preaching the most preferred is the lecture method, then followed by the method of giving examples. Furthermore, some like TV media and only a small proportion are interested in internet media and social media.